Analisis Kualitas Pelayanan E-KTP di Daerah Terpencil: Studi Kasus di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bulungan - Bambang Setiawan; Pardamean Daulay; Rina Yulianti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This study examines the quality of public service in the issuance of Electronic Identity Cards (e-KTP) at the Disdukcapil (Department of Population and Civil Registration) of Bulungan Regency, focusing on the challenges faced by communities in remote areas. The e-KTP, as an evolution of the conventional ID card, aims to enhance security and efficiency in population administration through electronic chip technology. The legal basis for the implementation of e-KTP in Indonesia is regulated by Law No. 24 of 2013, which mandates every citizen to possess an e-KTP. However, its implementation in the field still faces obstacles, particularly for residents in remote areas, who are forced to travel long distances to access services. The research employs a descriptive qualitative approach, analyzing based on five dimensions of service quality: reliability, assurance, tangibles, empathy, and responsiveness. Through interviews, observations, and documentation, the study finds that although staff possess technical competence and empathetic attitudes, there is a gap between expected service standards and the reality on the ground, particularly concerning infrastructure and service frequency. The findings indicate that the quality of e-KTP services in Bulungan Regency is still hindered by limited access and facilities, impacting the difficulties faced by the community in obtaining population documents. The dimension of empathy emerges as a positive aspect that enhances the community's experience; however, improvements in infrastructure and service systems are urgently needed to achieve equitable access. Therefore, this study provides recommendations for comprehensive improvements that include enhancing internet connectivity, physical facilities, and service frequency, so that e-KTP services can be more equitable and sustainable.